Den Danske Ordbog – en kritisk opsamling af den offentlige ordstrid - Pálfi, Loránd-Levente (LexicoNordica, 2005)
This paper will seek to summarize, unravel and take a critical position on what has been said, written and thought about Den Danske Ordbog [The Danish Dictionary]. The paper will refer to not only reviews, but also articles which in other ways deal with Den Danske Ordbog, or whose coming into existence is prompted by the publication of this dictionary. However, only the public criticism, i.e. not the scholarly criticism, shall be mentioned. Furthermore this paper proposes to give an account of the background and process of formation of this dictionary (discussed in chapter three), which is a precondition for a better understanding of the dictionary (discussed in chapter four), in turn a precondition for an understanding of the public criticism (discussed in chapter five).